Analisis Kinerja Petugas Apron Movement Control (AMC) Dalam Pengawasan Terhadap Ketertiban Ground Support Equipment (GSE) di Area Apron Pada Bandar Udara Internasional Adi Soemarmo Solo - Muhamad Ihsan Saputra (PT FORMOSA CENDEKIA GLOBAL, 2022)
The air transportation industry from year to year has developed quite significantly from time to time. The spread of LCC (Low Cost Carrier) air transportation that offers affordable prices has resulted in increased growth in demand for air transportation services. Apron Movement Control (AMC) is a supervisory unit for all aircraft traffic movements, with operations in the area, and the apron movement control (AMC) unit has a standard operating procedure (SOP). AMC plays an important role because it cannot be separated from aircraft movement activities while on the ground. To expedite all activities at the airport, good and adequate facilities and international standards are needed. The research method uses a descriptive method with a qualitative approach and data collection through interviews. The respondents of this study were Apron Movement Control (AMC) officers at Adi Soemarmo International Airport, Solo. This research was carried out on December 01-30, 2021, at Adi Soemarmo International Airport, Solo. The purpose of this study was to determine how much influence and efforts to improve the performance of AMC officers in supervising the orderliness of GSE officers in the apron area. The results of the research test show that efforts to improve the supervisory performance of the AMC unit are always based on the Adi Soemarmo Solo International Airport Aerodrome Manual SOP and 2019 KP 326 SOP which are the latest from the Directorate General of Civil Aviation. With a sanction or warning given by the AMC unit if an error is found, it has an effect on the Ground Support Equipment (GSE) operational unit to minimize errors002E